Efektifitas Daun Kubis Untuk Mengurangi Pembengkakan Payudara Masa Nifas di Wilayah Puskesmas Mataraman - Novalia Widiya Ningrum; Siti Rohani; Ika Avrilina Haryono (STIKes Payung Negeri Pekanbaru, 2023)
Background: One of the things that can cause obstacles in exclusive breastfeeding is the problem of breast swelling, this is affected by the shrinkage of the lactiferous ducts by glands that are not emptied properly, most feel the breasts are swollen, red, hard, painful, and feels hot. Cabbage leaf compresses on breasts that are experiencing swelling can be done as a non-pharmacological therapy, because it can reduce swelling in the breasts. Objective: To identify the effectiveness of cabbage leaves to reduce breast swelling during the puerperium in the Mataraman Health Center Work Area Methods: Type of research uses actual experiments in the form of a control-group pretest-posttest design. This study compared the effectiveness of giving cabbage leaf compresses with a decrease in the scale of swelling in the breasts between before and after giving cabbage leaf compresses with the control group. Results: The decrease in the scale of breast swelling after giving cabbage leaf compresses was measured in the morning, afternoon and evening. Afternoon is the time of greatest decrease with a scale of 2 (slight change in the breast), namely as many as 11 people (73.3%), while the rest are only 4 people (26.7%) with a scale of 1 (soft breasts, no change in the breast). Conclusion: Cabbage leaf compress therapy has the effectiveness of reducing breast swelling compared to the group that was not given. The optimal time for reducing swelling is in the afternoon.